Flourishing at work: Psychometric properties of the Polish version of the Workplace PERMA-Profiler - Paweł Fortuna; Agnieszka Czerw; Barbara Ostafińska-Molik; Agata Chudzicka-Czupała (PLoS ONE, 2025)
The main purpose of this study was to investigate the validity of the Polish version of the Workplace PERMA-Profiler (WPP). Our work was guided by Martin Seligman’s perspective on positive psychology, emphasizing well-being as its central theme, flourishing as the gold standard for measuring well-being, and the ultimate goal of increasing flourishing. According to his PERMA model, flourishing encompasses five key elements: positive emotions, engagement, relationships, meaning, and accomplishment. The WPP is a tool specifically designed to measure this construct in the workplace context. Polish workers completed online surveys at the initial measurement (N = 1070). In addition, a group of working adults (N = 66) took part in a survey with a repeated measure diagnosing measurement stability. Flourishing, perceived stress, and work satisfaction were measured for comparisons of convergent validity, while zero-sum belief was measured for divergent validity. The reliability indices of the Polish version of the WPP met the minimum reliability requirements, and the Confirmatory Factor Analysis indicated that the five-factor model (contrasted to the single-factor model) achieved the desired goodness-of-fit properties. The WPP also demonstrated convergent validity through strong interrelationships with related constructs and strong stability. Obtaining satisfactory psychometric properties of the Polish version of the WPP enabled the conduction of additional type of exploratory analyzes focused on the relationship between workplace flourishing and the efforts aimed at building employee well-being undertaken by the organization where the respondents work. The study revealed a positive, moderate relationship between employees’ flourishing and the evaluation of organizational practices for increasing employee well-being.